A cantilever-based resonator for reconfigurable nanomechanical computing. (12th November 2021) - Fang, Jiawei; Zhang, Pengcheng; Yang, Rui; Wang, Zenghui
Abstract: As silicon transistors face challenges in scaling, nanoelectromechanical systems (NEMS) have emerged as a promising candidate for computing due to the ultralow power consumption and high-temperature compatibility. Yet there is still limited research about highly reconfigurable NEMS-based computing devices that integrate multiple functionalities into a single device. In this work, we present the design, simulation, and verification of a cantilever-based NEMS resonator for highly reconfigurable logic functions. Using a single resonator with multiple inputs, the device can be reconfigured to perform AND, OR, XOR, and NOT logic operations, by changing the combination of inputs. We use both DC and AC voltages as inputs, where AC inputs can be used for better reconfigurability, and DC inputs offer higher On/Off ratio. The cantilever structure has low rigidity and large dynamic range, and thus only requires 5 mV of AC drive to achieve relatively large vibration amplitude. This work presents a unique platform where a single NEMS resonator can be used for reconfigurable computing.